Transcriptomic Analysis Revealed Reactive Oxygen Species Scavenging Mechanisms Associated With Ferrous Iron Toxicity in Aromatic Keteki Joha Rice - Regon, Preetom; Dey, Sangita; Rehman, Mehzabin; Pradhan, Amit Kumar; Chowra, Umakanta; Tanti, Bhaben; Talukdar, Anupam Das; Panda, Sanjib Kumar (Frontiers in Plant Science, 2022)
Lowland acidic soils with water-logged regions are often affected by ferrous iron (Fe2+) toxicity, a major yield-limiting factor of rice production. Under severe Fe2+ toxicity, reactive oxygen species (ROS) are crucial, although molecular mechanisms and associated ROS homeostasis genes are still unknown. In this study, a comparative RNA-Seq based transcriptome analysis was conducted to understand the Fe2+ toxicity tolerance mechanism in aromatic Keteki Joha. About 69 Fe homeostasis related genes and their homologs were identified, where most of the genes were downregulated. Under severe Fe2+ toxicity, the biosynthesis of amino acids, RNA degradation and glutathione metabolism were induced, whereas phenylpropanoid biosynthesis, photosynthesis, and fatty acid elongation were inhibited. The mitochondrial iron transporter (OsMIT), vacuolar iron transporter 2 (OsVIT2), ferritin (OsFER), vacuolar mugineic acid transporter (OsVMT), phenolic efflux zero1 (OsPEZ1), root meander curling (OsRMC) and nicotianamine synthase (OsNAS3) were upregulated in different tissues, suggesting the importance of Fe retention and sequestration for detoxification. However, several antioxidants, ROS scavenging genes and abiotic stress-responsive transcription factors indicate ROS homeostasis as one of the most important defense mechanisms under severe Fe2+ toxicity. Catalase (CAT), glutathione (GSH), ascorbate peroxidase (APX), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR) and glutathione reductase (GR) were upregulated. Moreover, abiotic stress-responsive transcription factors no apical meristem (NAC), myeloblastosis (MYB), auxin response factor (ARF), basic helix-loop-helix (bZIP), WRKY, C2H2-zinc .nger protein (C2H2-ZFP) were also upregulated. Accordingly, ROS homeostasis has been proposed as an essential defense mechanism under such conditions. Thus, the current study may enrich the understanding of Fe-homeostasis in rice.